Professional and Personal Well-Being Among Members of a Christian Organization for Healthcare Providers: A Cross-Sectional Study - Stephanie L. Harris; Ted Hamilton; Hong Tao; Carla Gober Park (Religions, 2025)
Objectives: To determine the aspects of religion and spirituality among those who belong to an organization for Christian healthcare providers that may contribute to personal and professional well-being and protect against burnout. Participants: Members and affiliates of the Christian Medical and Dental Association (n = 450). Study Method: A cross-sectional study based on survey results of validated instruments and original questions that measured aspects of faith, professional fulfillment, personal fulfillment, and mental health. Findings: This sample of Christian healthcare providers experienced lower rates of burnout than the general population of healthcare providers. Personal aspects of religion and spirituality were negatively associated with anxiety and depression and positively associated with personal flourishing. Conclusions: Calling, virtues, and belonging are possible attributes of Christian faith that are associated with well-being and may be protective against burnout and mental health conditions. Future research can explore these findings among providers of other faith traditions.